Epigenetic Profile of Human Adventitial Progenitor Cells Correlates With Therapeutic Outcomes in a Mouse Model of Limb Ischemia. Issue 3 (March 2015) - Gubernator, Miriam; Slater, Sadie C.; Spencer, Helen L.; Spiteri, Inmaculada; Sottoriva, Andrea; Riu, Federica; Rowlinson, Jonathan; Avolio, Elisa; Katare, Rajesh; Mangialardi, Giuseppe; Oikawa, Atsuhiko; Reni, Carlotta; et al.
Abstract : Objective—: We investigated the association between the functional, epigenetic, and expressional profile of human adventitial progenitor cells (APCs) and therapeutic activity in a model of limb ischemia. Approach and Results—: Antigenic and functional features were analyzed throughout passaging in 15 saphenous vein (SV)–derived APC lines, of which 10 from SV leftovers of coronary artery bypass graft surgery and 5 from varicose SV removal. Moreover, 5 SV-APC lines were transplanted (8×10 5 cells, IM) in mice with limb ischemia. Blood flow and capillary and arteriole density were correlated with functional characteristics and DNA methylation/expressional markers of transplanted cells. We report successful expansion of tested lines, which reached the therapeutic target of 30 to 50 million cells in ≈10 weeks. Typical antigenic profile, viability, and migratory and proangiogenic activities were conserved through passaging, with low levels of replicative senescence. In vivo, SV-APC transplantation improved blood flow recovery and revascularization of ischemic limbs. Whole genome screening showed an association between DNA methylation at the promoter or gene body level and microvascular density and to a lesser extent with blood flow recovery. Expressional studies highlighted the implication of an angiogenic network centered on the vascular endothelial growth factor receptor as a predictor of microvascular outcomes. FLT-1 gene silencing in SV-APCs remarkably reduced their ability to form tubes in vitro and support tube formation by human umbilical vein endothelial cells, thus confirming the importance of this signaling in SV-APC angiogenic function. Conclusions—: DNA methylation landscape illustrates different therapeutic activities of human APCs. Epigenetic screening may help identify determinants of therapeutic vasculogenesis in ischemic disease. Abstract : Supplemental Digital Content is available in the text.